Melchior Goldast und der 'Codex Manesse' Mit besonderer Berücksichtigung seiner 'Hypomnemata in aulicorum Poetarum Carmina amatoria' - Wolbring, Michael (Heidelberg University Publishing (heiUP), 2019)
In the period around 1600, the Swiss humanist and lawyer Melchior Goldast von Haiminsfeld (1576/78-1635) focuses his scholarly work on the literature of the Middle Ages. His attention is particularly drawn to the most important medieval lyric manuscript in German, the Codex Manesse. Goldast makes extensive notes on the manuscript, quotes from it and edits parts of it, thus making it known to a wider public for the first time. Rather than an enthusiasm for the poetry of the Middle Ages, however, it is above all his interest in the politics of the day that motivates the Calvinist Goldast.